The clinical and functional outcomes of a large naturalistic cohort of young people accessing national early psychosis services. (October 2022) - Brown, Ellie; Gao, Caroline X.; Staveley, Heather; Williams, Georgia; Farrelly, Simone; Rickwood, Debra; Telford, Nic; Papanastasiou, Cerissa; McGorry, Pat; Thompson, Andrew
Aims: Services for individuals with a first episode of psychosis or at ultra-high risk of psychosis have become a treatment model of choice in mental health care. The longitudinal changes in clinical and functional outcomes as a result of real-world treatment remain under-reported. Methods: We analysed data from first episode of psychosis and ultra-high risk services delivered across Australian primary youth mental health care services known as headspace between 19 June 2017 and 30 September 2019. Outcome measures were completed and entered into a minimum dataset every 90 days a participant was receiving treatment and included psychiatric symptomatology (Brief Psychiatric Rating Scale and psychological distress, K10) and psychosocial functioning (Social and Occupational Functioning Assessment Scale and My Life Tracker). Linear mixed-effects models were used to evaluate changes in outcome over time. Results: Outcome data from a total of 1252 young people were evaluated (643 first episode of psychosis, 609 ultra-high risk). Of those who entered ultra-high risk services, 11.8% transitioned to first episode of psychosis services. Overall, substantial improvement in clinical (Brief Psychiatric Rating Scale, K10) and functional (Social and Occupational Functioning Assessment Scale, My Life Tracker) outcomes were seen across groups and outcomes. Ultra-high risk patients showed a greater reduction in distress symptoms, while first episode of psychosis patients experienced a greater reduction in positive psychosis symptoms. Although clinical outcomes showed a plateau effect after approximately 3 months of care, improvement in functional outcomes (Social and Occupational Functioning Assessment Scale, My Life Tracker) continued later in treatment. Conclusion: These findings support the use of real-time, real-world and low-cost administrative data to rigorously evaluate symptomatic and functional outcomes in early psychosis treatment settings. Findings that functional outcomes improve past the remittance of clinical outcomes also support the functional recovery focus of early psychosis services and remaining high levels of distress suggest the need for ultra-high risk services to extend beyond 6 months of care.